(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In a scientific article to reveal from new perspectives and research one of the events that left a significant mark on the history of Central Asia - the battle that took place near the city of Atlakha on the Talas River in 751. The city of Atlakh, one of the largest cities on the Great Silk Road in the Middle Ages, is currently located in the village of Joon-Tobe, Manas district, Talas region of Kyrgyzstan. Therefore, this historical event is not only for Kyrgyzstan, it is known that it left a deep mark in Central and Inner Asia, Siberia and Altai as a whole. Therefore, the analysis was carried out on the basis of some sources in order to clarify the historical position in the article. The history and interpretation of the runic stone monument in the area where the Battle of Atlach took place was further researched and supplemented in the article.